Correlation between Prognostic Factors and the Histopathological Response to Neoadjuvant Chemotherapy in Osteosarcoma: A Retrospective Study. (27th April 2021) - Prabowo, Yogi; Setiawan, Iwan; Kamal, Achmad Fauzi; Kodrat, Evelina; Labib Zufar, Muhammad Luqman
Abstract : Background. Multimodality treatment, incorporating neoadjuvant chemotherapy and adjuvant chemotherapy, is the standard management plan for osteosarcoma that increases the overall survival (OS) rate. However, data regarding prognostic factors affecting the histopathological response following neoadjuvant chemotherapy is limited. Patients and Methods. We retrospectively reviewed patients diagnosed with osteosarcoma in our center between 2008 and 2018. We classified patient characteristics according to gender, age, tumor size, site and stage at diagnosis, site of metastasis, type of surgery, necrosis rate based on the Huvos grading system, and the number of neoadjuvant chemotherapy cycles. We divided response to neoadjuvant chemotherapy into poor responder for patients with Huvos grades 1 and 2 and good responder for patients with Huvos grades 3 and 4. We also documented patients' survival and follow-up information. Results. We reviewed 64 patients within 5–65 years of age, dominated by men (62.5%). The distal femur (53.1%) was the most common site of osteosarcoma. Fifteen (23.4%) patients had a good response while 49 (76.6%) patients were poor responders to neoadjuvant chemotherapy based on the Huvos grading system. Based on multivariate analysis, gender (p = 0.012), age (p = 0.029), symptom duration (p = 0.004), and tumor enlargement after neoadjuvant chemotherapy (p < 0.001) were significantly associated with histopathological response. A scoring system was proposed integrating these significant variables (age > 20 years = 1 point, female gender = 1 point, symptom duration > 12 weeks = 1 point, and increased tumor size after neoadjuvant chemotherapy = 2 points). This scoring system divides patients into two groups with a total score of more than two predicting a poor responder to neoadjuvant chemotherapy. Conclusions . Age, gender, symptoms duration, and tumor size after neoadjuvant chemotherapy are the prognostic features that affect the histopathological response to neoadjuvant chemotherapy in patients with osteosarcoma.